Penerapan Model Pembelajaran STAD Berkombinasi Scaffolding untuk Meningkatkan Hasil Belajar Kognitif Mata Pelajaran Pendidikan Pancasila - Muzaki, Alfian Nur; Fadlillah, M.; Matwani, Matwani (YASIN, 2025)
This research was conducted due to the limitations of studies regarding the improvement of cognitive scores from the STAD learning model with the assistance of scaffolding strategies. The application of scaffolding strategies in learning has a positive impact on improving the cognitive learning outcomes of students. This study aims to determine the cognitive learning outcomes of sixth-grade students at the UPTD SDN Keleyan 1 by applying the STAD learning model combined with scaffolding strategies in the subject of Pancasila Education. The research method used is classroom action research (PTK) with a participative type. The target of the study is the sixth grade, consisting of 19 students. Data collection was carried out through observation, tests, and documentation, with data analysis using quantitative descriptive techniques. The results of the study indicate that the STAD learning model combined with scaffolding can improve cognitive learning outcomes in the subject of Pancasila Education through two cycles. There was an improvement from the pre-cycle phase to cycle I of 14.22, with an average score of cycle I of 62.11 and a percentage increase of 29.69%. Furthermore, from cycle I to cycle II, there was a larger increase of 16.84, with an average score of 78.95 and a percentage increase of 27.11% using scaffolding. The main conclusion of this study is the importance of applying scaffolding in an appropriate learning model, one of which is the STAD learning model, to address the cognitive learning outcome gaps of students in the subject of Pancasila Education. The implications of this research are the improvement of cognitive learning outcomes and the application of scaffolding with the STAD learning model to assist students with low cognitive abilities in achieving learning independence. This research can also open up further studies regarding the affective and psychomotor aspects in the application of scaffolding strategies.